2017
DOI: 10.1177/1533034617707598
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation: A Linchpin in Radiation-Induced Enteritis

Abstract: Radiation enteritis is one of the most feared complications of abdominal and pelvic regions. Thus, radiation to abdominal or pelvic malignancies unavoidably injures the intestine. Because of rapid cell turnover, the intestine is highly sensitive to radiation injury, which is the limiting factor in the permissible dosage of irradiation. Bowel injuries such as fistulas, strictures, and chronic malabsorption are potentially life-threatening complications and have an impact on patient quality of life. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…It was found these mRNAs function mainly in the biological processes of cytokine and cell secretion, which may be associated with radiation-induced enteritis [37]. Some researchers have compared inflammatory bowel disease and normal segments of colon from patients with radiation proctitis against normal controls and found that radiation-induced tissue damage is associated with elevated levels of interleukins, especially interleukin-1β [38].…”
Section: Discussionmentioning
confidence: 99%
“…It was found these mRNAs function mainly in the biological processes of cytokine and cell secretion, which may be associated with radiation-induced enteritis [37]. Some researchers have compared inflammatory bowel disease and normal segments of colon from patients with radiation proctitis against normal controls and found that radiation-induced tissue damage is associated with elevated levels of interleukins, especially interleukin-1β [38].…”
Section: Discussionmentioning
confidence: 99%
“…There is no concrete evidence to suggest that higher quantities of antioxidants are beneficial. 8 Treatment depends on the pattern of the symptoms involved. Controlling diarrhoea involves use of anti-diarrhoeal agents such as loperamide 9 and, if ongoing, the addition of bile acid sequestrants can be helpful.…”
Section: Radiotherapy-related Enteritismentioning
confidence: 99%
“…Ninety percent of patients present with ARII, and subsequently, 5% to 55% develop CRII post-pelvic radiotherapy. [6][7][8] Most of the symptoms of ARII are transient, self-healing, and relieved within 3 months. While CRII often emerges 12~24 months after the end of radiotherapy, it is progressive and difficult to reverse.…”
Section: Introductionmentioning
confidence: 99%